Restructuring Religious Education for Development Sustainability in the 21st Century Nigeria - Alaka-Osinowo, Bolayemi. O. S. (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
The importance of education to national development and growth especially in Nigeria cannot be overlooked. It plays vital roles in the resources essential for societal growth and it should be noted that these resources include human resources as individuals are responsible for nation building. Education comprises basic knowledge and skills required for sustainable living. These knowledge and skills constitute moral values and codes which are learnt through religious education. Hence, religious education remains vital and relevant particularly in the 21st century Nigeria. In the 21st century, religious education in Nigeria continues to experience problems ranging from the implementation of irrational educational policies by the constituted authorities particularly against educational system, poor funding, mismanagement and misappropriation, political instability, bad governance, just to mention a few. It is not a dispute that these lingering issues have indented the place of religious education and its values in the educational system which has been debased. Nevertheless, acquiring quality education should be measured on global standards, such that the acquired knowledge could match up with the global scale. Therefore, it is crucial to revisit and reconstruct religious education particularly to conform to the 21st century Nigerian society. This is to attain a stable and life - long relevance within the Nigerian educational system. It is a qualitative discourse and it engages primary and secondary sources of data information, it adopts the functional theory which spells out the functions of religious education to the national development particularly in the 21st century as well as the theory of relevance which reflects the relevance of religious education as tool to instill morals and mould individuals into good and patriotic citizens. It includes discussions on the challenges militating against religious education in the 21st century. The relevance of religious education at this era, and recommended suggestable strategies to sustain its relevance further into the future.